(untitled) (Journal on Geoinformatics, Nepal, 2003)
Remote sensing may be broadly defined as acquiring and then interpreting information about objects, which are away from the sensor. Geographic Information System (GIS) is a tool for integrating and analyzing spatially referenced geo-spati al data. The integration of remote sensing and GIS technology provides an opportunity for characterizing and analyzing dynamic environments so that any change of objects in terms of geometry, class and topology can be identified. Updating of the vector data of scale 1:25000 of Enschede Municipality, the Netherlands by using remotely sensed Ikonos imagery was performed by simultaneous viewing them using GIS tool. It is found that remote sensing high optical imagery are of promising characteristics in terms of capturing feature so that updating of vector is possible and database can be maintained easily and comparatively in less time than by using the field surveying techniques.